Brand personality and consumer self-expression: single or dual carriageway? - Phau, Ian (Henry Stewart Publications, 2001)
Considerable research into consumer behaviour has examined the self-expressive role of brands, but has found little support for the premise that brand personality has an influence on consumer attitudes. This paper thus proposes that consumers have a part to play in influencing how a brand personality is perceived. This is in contrast to other research and propositions, which suggest that brand personality is created by how marketers and advertisers intend to project it. The findings suggest that when a brand commands a high preference, the preferred personality of the consumers actually has an influence over its perceived brand personality — provided that the consumer has built a positive relationship with the brand and then reinforces his/her personality on to the brand. The research also illustrated that the individualist’s ‘self’ has a stronger positive influence on the perceived personality of their preferred brand as compared to collectivists. The findings from this research shed light on the self-expressive use of brands, and the effects of the cultural orientation of consumers in influencing the relationship between their self and the perceived brand personality of their preferred brand. Marketers must strategically position their brands to provide a vehicle for consumers to experience emotional benefits, subsequently leading to stronger brand equity.